Silverfil: its physical characterization - Abu Kasim, Noor Hayaty; Yahya, N.A.; Radzi, Z.; Basirun, Wan Jefrey; Ghani, A.A. (Springer, 2007)
This article focuses on the physical characterization of Silverfil (R) amalgam. Analysis of the amalgamated material semi-quantitatively showed that Silverfil (R) comprised of approximately two thirds mercury and one third silver. No other elements were detected. Examination of the amalgamated material by x ray mapping and metallographically showed no evidence of free mercury present. Silverfil (R) has strong affinity towards the mercury ion. X-ray Diffraction analysis showed that the amalgamated Silverfil (R) is similar to a mineral in nature called "Moschellandsbergite". The advantages of Silverfil (R) over conventional amalgam were highlighted.